Current and selected issues in banking, taxes and accounting - Ćwiąkała-Małys, Anna. Red.; Rutkowska-Tomaszewska, Edyta. Red.; Zalcewicz, Anna. Rec. (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This monograph presents issues selected issues from among the most topical in the area of banking, taxes, and accounting, examined from the perspective of both economics and law. Among the issues related to banking and the financial markets in general, there is a presentation of the structure of domestic legal regulations as they concern prudential norms in conjunction with the necessity of adapting them to the so-called “CRD IV/CRR package”, legal regulation concerning interchange fees as adopted in the Regulation of the European Parliament and the Council regarding interchange fees for payment transactions performed using payment cards. Concerning the issue of taxes, there is a discussion of both issues regarding payment for consideration in VAT and the application of this tax to grants received by private entities for the performance of tasks assigned by local self-government agencies, in the areas of social assistance and educational services, and also taxation of grants for cultural institutions. There is also a discussion of taxation of agricultural activity, both from a historical perspective and a current one discussing contemporary trends, taxation of real property by communes, and the general tax avoidance clause. The third area of deliberations consists of issues surrounding management of finances and accounting. It contains a presentation of the issue of the role of financial reporting in assessment of the financial situation of an enterprise and management of that enterprise; the manner in which costs for management of an enterprise can be deducted using the example of a publisher, and the possibilities for financing activity involving the transfer of technology to commercial practice. There is also a presentation of the tax and the accounting definitions of income and costs resulting from so-called excess performance of medical services that arises after exceeding the limit of services defined in the contract between service providers and the National Health Fund.
Keywords: prudential norms; CRD IV/CRR; interchange fee; Venture Capital; technology transfer; costs of doing business; cost accounting; financial report; balance; profit and loss statement; grant; value added tax; real property tax; agricultural taxes; agricultural accounting; tax avoidance; general clause; cultural institutions; medical service providers; excess performance